2017
DOI: 10.1080/00029157.2016.1172057
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis as a Valuable Tool for Surgical Procedures in the Oral and Maxillofacial Area

Abstract: Hypnosis is a valuable tool in the management of patients who undergo surgical procedures in the maxillofacial complex, particularly in reducing and eliminating pain during surgery and aiding patients who have dental fear and are allergic to anesthesia. This case report demonstrates the efficacy of hypnosis in mitigating anxiety, bleeding, and pain during dental surgery without anesthesia during implant placement of tooth 14, the upper left first molar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Clinical experience and experimental studies have shown that hypnotic suggestions can significantly modify the perception of our internal and external world. There is clear evidence that people can completely relieve from pain with the help of hypnotically induced hypoalgesic suggestions either during surgical interventions like cataract surgery [ 1 , 2 ], bone marrow aspirations, lumbar punctures and voiding cystourethograms (for all these examples see: [ 3 ]), or dental surgery [ 4 , 5 ]. Other examples are provided by hypnotized fakirs [ 6 , 7 ] and Tamil believers [ 8 , 9 ] in hypnotic trance who painlessly are stabbing knives or lances into their body in expectation of divine assistance, grace, or forgiveness from sins.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical experience and experimental studies have shown that hypnotic suggestions can significantly modify the perception of our internal and external world. There is clear evidence that people can completely relieve from pain with the help of hypnotically induced hypoalgesic suggestions either during surgical interventions like cataract surgery [ 1 , 2 ], bone marrow aspirations, lumbar punctures and voiding cystourethograms (for all these examples see: [ 3 ]), or dental surgery [ 4 , 5 ]. Other examples are provided by hypnotized fakirs [ 6 , 7 ] and Tamil believers [ 8 , 9 ] in hypnotic trance who painlessly are stabbing knives or lances into their body in expectation of divine assistance, grace, or forgiveness from sins.…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura, até o momento, não foram encontrados estudos científicos com relatos da hipnoterapia em procedimentos estéticos. Porém, já é de conhecimento cientifico a eficácia da hipnoterapia em procedimentos odontológicos para analgesia (LUCAS, 2014;MONTENEGRO et al, 2017), como também para acesso venoso (HILTUNEN et al, 2019).…”
Section: Resultsunclassified
“…O estudo de Hiltunen et al (2019), selecionou 148 pessoas que passaram por uma cirurgia de implantação por porta de acesso venoso, após 26 minutos de hipnose, concluiu que uma sessão de hipnose melhorou significativamente a satisfação dos mesmos. Montenegro et al (2017) em um procedimento, induziu uma paciente a anestesia hipnótica durante um implante dentário, não fazendo o uso de anestesia farmacológica local. Logo após o procedimento e dentro de 24 horas não houve sangramento, edema, eritema e relato de dor, concluiu que a hipnoterapia foi eficaz em procedimentos cirúrgicos odontológicos na redução da ansiedade, sangramento e dor, minimizando o uso de anestésicos e efetuando o melhor resultado pósoperatório.…”
Section: Resultsunclassified
“…Makovac et al reported as hypnosis combined with local anesthesia provides an effective alternative in selected patients with very high anesthesiological risk [ 5 ]. Montenegro et al indicate hypnosis as a valuable tool in pain management of patients subjected to surgical procedures in the maxillofacial complex [ 6 ]. Werner et al conducted a RCT with 1222 nulliparous women reporting that a brief course in self-hypnosis clinically improved the women's childbirth experience [ 7 ].…”
Section: Fourth Phase - Exit From Hypnosis and Reorientation (10 Min)mentioning
confidence: 99%